An Introduction to Sociocultural Anthropology : Adaptations, Structures, Meanings - Haines, David W. (Book collections on Project MUSE., 2017)
"A concise yet comprehensive guide to cultural anthropology using a materialist approach. This revised and updated edition exposes students to the cultural detail and personal experiences that lie in the anthropological record and extends their anthropological understanding to contemporary issues"--Provided by publisher.